2002
DOI: 10.1034/j.1600-0625.2002.110608.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frequency of intracellular IFN‐γ producing T cells in whole blood preparations from patients with atopic dermatitis

Abstract: Decreased frequency of intracellular IFN-gamma producing T cells in whole blood preparations from patients with atopic dermatitis.Källström, Eva; Roscher, Ingrid; Andreasson, Annica; Bäck, Ove; Van Hage-Hamsten, MariannePublished in: Experimental Dermatology DOI: 10.1034/j. 1600-0625.2002.110608.x 2002 Link to publication Citation for published version (APA): Källström, E., Roscher, I., Andreasson, A., Bäck, O., & Van Hage-Hamsten, M. (2002). Decreased frequency of intracellular IFN-gamma producing T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
0
24
1
1
Order By: Relevance
“…The results presented in our report differ from most studies, which demonstrate increased IL-4 production and decreased IFN-γ by PBMC after in vitro polyclonal stimulation in AD patients compared with nonatopic subjects [9,28,29,36]. In contrast, Källström et al [18] showed decreased frequency of intracellular IFN-γ-and IL-4-producing T cells in whole blood preparations from adult patients with AD. Moreover, Fig.…”
Section: Discussioncontrasting
confidence: 82%
“…The results presented in our report differ from most studies, which demonstrate increased IL-4 production and decreased IFN-γ by PBMC after in vitro polyclonal stimulation in AD patients compared with nonatopic subjects [9,28,29,36]. In contrast, Källström et al [18] showed decreased frequency of intracellular IFN-γ-and IL-4-producing T cells in whole blood preparations from adult patients with AD. Moreover, Fig.…”
Section: Discussioncontrasting
confidence: 82%
“…92 The view of AD as a prototypical T H 2 disease was supported by multiple observations, including increased levels of T H 2 products, 111 relatively reduced antimicrobial peptide (AMP) levels in skin compared with levels seen in patients with psoriasis, 88 and low levels of IFN-g in blood samples from patients with AD. 112 This led to clinical trials in patients with severe AD with recombinant IFN-g, which was suggested to restore the T H 1/T H 2 balance but was effective in only a subset of patients. 113 Although successful in treating patients with psoriasis, 57 disappointing 115 arguing against a major pathogenic role of TNF in patients with AD.…”
Section: Evolving Pathogenic Concepts In Admentioning
confidence: 99%
“…A minimum of 3,000 cells was analyzed within the lymphocyte cluster, and the results are expressed as a percentage of cytokine-producing cells in a population of speciWed T helper cells, i.e., CD3 and CD4 positive cells (Källström et al 2002).…”
Section: Analysis Of Nasal Lavage and Blood Testsmentioning
confidence: 99%